Taxonomic update and first record of Aphelandra martiusii (Acanthaceae) in Peru - Villanueva-Espinoza, Rosa (2022)
A taxonomic update is provided for Aphelandra martiusii (Acanthaceae), a poorly known species from the Amazon Forest. The species was previously known from Brazil and Colombia and it is recorded for the first time in the Department of Loreto, Peru. The name A. martiusii is lectotypified by a specimen housed at Staatliche Naturwissenschaftliche Sammlungen Bayerns (M). A detailed morphological description, photographs, a line drawing, a distribution map, and a discussion on the taxonomy, geographic distribution, and conservation status of this species are provided.